Strategi Pembelajaran Practice Rehearsal Pairs dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran TIK Kelas VIII di SMP Negeri 2 Ungaran - Nurrika, Aswita; Sutarno, Sutarno; Sudana, I Made (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
This study aims to determine the increase in student learning outcomes SMPN 2 Ungaran through the application of Practice Rehearsal Pairs learning strategies on the subjects of ICT Class VIII Junior High School 2 Ungaran. This research is classified as quasi-experimental research with Nonequivalent Control Group Design. The population in this study are all students of class VIII SMPN 2 Ungaran totaling 298 students. Samples were taken by purposive sampling with F VIII class as the experimental class and I class VIII as the control class with the number of 68 students. Data were analyzed using independent sample t-test test and n-gain test. The results showed that increased cognitive achievement of students in the experimental class is greater than the control class with n-gain experimental class > n-gain control class with 0.74> 0.62. In addition, there is an increased learning outcomes in the affective and psychomotor aspects of the experimental class larger than the control class. This shows that Practice Rehearsal Pairs learning strategies better than conventional learning. Suggestions based on the achievement of the implementation of Practice Rehearsal Pairs learning strategies in the learning process which can be used as an alternative in implementing learning in school and to the subsequent researchers to further develop the application of learning strategies Practice Rehearsal Pairs on subsequent learning process.